Copper niobate doped solid magnesium-based hydrogen storage material as well as preparation method and application thereof
By doping copper niobate in magnesium-based hydrogen storage materials and distributing catalysts by ball milling method, the problem of difficult optimization of hydrogen absorption and hydrogen discharge performance of magnesium-based hydrogen storage materials is solved, and the improvement of low-temperature hydrogen storage performance and kinetic performance are achieved Improvement.
Patent Information
- Application Number
- CN202411382264.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing magnesium-based hydrogen storage materials have high thermodynamic stability and slow kinetic reactions, which limit their feasibility in practical applications, especially the hydrogen absorption and hydrogen discharge performance are difficult to optimize simultaneously.
By doping copper niobate (CuNb2O6) into MgH2, and uniformly distributing the copper niobate catalyst by ball milling, the hydrogen absorption and release rate and kinetic performance of MgH2 are significantly improved, forming a composite material with excellent low-temperature hydrogen storage performance.
The hydrogen absorption and hydrogen release rate of MgH2 has been significantly improved, achieving joint optimization of kinetics and total amount. Compared with single metal oxides and other bimetallic elements, the catalytic improvement effect is more significant, and it is a new type of magnesium-based composite hydrogen storage The material provides an effective strategy.
Smart Images

Figure CN119263208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of hydrogen storage materials, and relates to a copper niobate-doped solid magnesium-based hydrogen storage material and a preparation method and application thereof. Background Art
[0002] As environmental and energy security issues become increasingly prominent, many countries are increasing their investment in renewable energy. Clean energy, such as solar, wind and hydropower, emits almost no greenhouse gases and helps reduce carbon emissions in the entire energy industry. The growing demand for clean energy has driven technological innovation in the fields of renewable energy generation, storage and distribution. In this context, hydrogen energy has attracted much attention due to its high energy density (33kWh / Kg), high calorific value, light weight, environmental friendliness and versatility, and is an attractive clean energy carrier. At the same time, hydrogen reserves are abundant and widely available, and the only reactant after combustion is water, without harmful gases, achieving zero emissions, which helps mitigate climate change and improve air quality. As one of the promising solutions to energy challenges, hydrogen energy is expected to make important contributions to the world's move towards a more sustainable and low-carbon future by closely integrating with renewable energy, regulating and storing energy through hydrogen energy to solve the instability of renewable energy.
[0003] At present, hydrogen storage methods can be divided into three categories: high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage, and solid-state hydrogen storage. Solid-state hydrogen storage uses the interaction between solids and hydrogen to store hydrogen. Compared with the other two hydrogen storage methods, solid-state hydrogen storage has a higher volumetric hydrogen storage density, higher safety and stability. In recent years, magnesium-based hydrogen storage materials have broad application prospects due to their excellent hydrogen storage capacity, good reversibility and low cost. Despite these advantageous properties, they are restricted by their high thermodynamic stability and slow kinetic reaction, which reduces the feasibility of their practical application. Therefore, it is necessary to optimize and modify them to meet the requirements of practical applications. At present, magnesium-based hydrogen storage materials are mainly optimized and modified from the aspects of alloying, nano-sizing, catalyst doping and composite.
[0004] Catalysts can increase the adsorption rate of metals / alloys without participating in chemical reactions, simply by reducing the activation energy barrier. In some cases, catalysts can also participate in chemical reactions, but remain unchanged after the reaction. To date, catalysts for several different hydrogen storage materials have been developed, which can be mainly divided into the following categories: (1) transition metal elements (transition metal elements have a significant common feature, that is, their valence electrons are sequentially filled in the sub-outer d orbital. This special electronic configuration structure exhibits unique physical and chemical properties and has a good catalytic effect on improving the hydrogen storage performance of MgH2. Pozzo et al. found through DFT calculations that all transition metals exhibit two opposite catalytic activities at the same time. For metals that promote dissociation effectively, diffusion has no effect, and vice versa); (2) transition metal oxides; (3) transition metal halides; (4) transition metal carbides, etc.; (5) carbonaceous materials, etc.
[0005] Transition metal oxides are excellent catalysts. Oelerich et al. used 5 mol% of metal compounds such as Sc2O3, TiO2, V2O5, Cr2O3, Mn2O3, Fe3O4, CuO, Al2O3 and SiO2 as catalysts for MgH2. They found that all compounds enhanced the adsorption kinetics, among which Cr2O3 had the best hydrogen absorption effect, while V2O5 and Fe3O4 had the best desorption effect. Barkhordarian et al. found that after MgH2 was doped with 0.5 mol% Nb2O5, it could achieve complete absorption and desorption of hydrogen (about 7 wt.%) within 60s and 90s at 300°C, respectively, which was much better than other transition metal oxides. Hanada et al. studied the room temperature hydrogen absorption kinetics of Nb2O5-catalyzed magnesium. Even at room temperature, the composite material doped with 1 mol% Nb2O5 could absorb 4.5 wt% H2 within 15s under 1MPaH2 pressure. Then, Kimura et al. used mesoporous Nb2O5 as a catalyst and achieved further improvements, absorbing H2 even at -50 °C, with activation energies of 70 kJ / mol and 38 kJ / mol for desorption and absorption, respectively. It is believed that the reduction of Nb2O5 to low-valent Nb compounds, namely NbO2 and NbO, may be the reason for the reduction in activation energy. Friedrich et al. proposed another possible mechanism, arguing that in addition to Nb and MgO, MgNb2O was formed during the first adsorption cycle. 3.67 phases, all of which contribute to the kinetic enhancement of MgH2. In recent years, the synergistic effect of bimetallic compounds has received increasing attention. Studies have shown that active catalytic species can be generated in situ by adding bimetallic compounds during ball milling and reaction.
[0006] Although single metal oxides can improve the performance of MgH2's hydrogen absorption and desorption ends, they can only significantly optimize one aspect of hydrogen absorption or desorption, and cannot take into account both ends at the same time. Pure MgH2 has high thermodynamic stability (ΔH-76kJ / mol, ΔS-130kJ / mol) and slow kinetics (Ea-161kJ / mol). It can only absorb and desorb hydrogen at a temperature of about 623K, which is difficult to meet the needs of practical applications and requires further modification.
[0007] As a transition metal element with catalytic activity, Nb has good performance in catalyzing the hydrogen storage performance of MgH2, but the catalytic effect of a single metal on the hydrogen absorption and desorption performance has certain limitations. The catalytic performance of transition metals can be further enhanced by utilizing the synergistic catalytic effect produced by the catalytic properties of different transition metals. Cu, as a transition element with a significant catalytic effect at the hydrogen desorption end, is expected to further enhance the performance of Nb-based catalysts in hydrogen desorption kinetics. Therefore, it is necessary to further study the method of doping MgH2 with CuNb2O6 catalyst to improve the hydrogen storage kinetics and cycle performance of MgH2. Summary of the invention
[0008] In view of this, one of the objects of the present invention is to provide a copper niobate-doped solid magnesium-based hydrogen storage material; a second object of the present invention is to provide a method for preparing a copper niobate-doped solid magnesium-based hydrogen storage material; a third object of the present invention is to provide an application of a copper niobate-doped solid magnesium-based hydrogen storage material in hydrogen storage.
[0009] In order to achieve the above object, the present invention provides the following technical solutions:
[0010] 1. A copper niobate-doped solid magnesium-based hydrogen storage material, the solid magnesium-based hydrogen storage material comprising MgH2 and doped copper niobate (CuNb2O6);
[0011] The mass ratio of MgH2 to copper niobate is 0.91:0.09 to 0.97:0.03.
[0012] Preferably, the copper niobate (CuNb2O6) is prepared according to the following method:
[0013] (1) Dissolve niobium oxide (Nb2O5) in hydrofluoric acid (HF), heat and stir to dissolve it, add ammonia water (NH3·H2O) while stirring, react for 10 minutes, filter and wash to obtain a white precipitate;
[0014] (2) adding the white precipitate and citric acid (CA) into water, heating and stirring to dissolve them, adding copper nitrate trihydrate (Cu(NO3)2·3H2O), continuing heating and stirring to mix them evenly, and vacuum drying;
[0015] (3) The vacuum-dried solid obtained in step (2) is placed in a muffle furnace and calcined to obtain copper niobate (CuNb2O6).
[0016] Further preferably, in step (1), the molar ratio of niobium oxide (Nb2O5) to aqueous ammonia is less than or equal to 1:1, and the heating and stirring temperature is 75-85°C and the time is 25-35 min.
[0017] Further preferably, the molar mass ratio of niobium oxide (Nb2O5) in step (1) to citric acid (CA) and copper nitrate trihydrate (Cu(NO3)2·3H2O) in step (2) is 1.5:7.5:1.5-2.5:12.5:2.5, mmol:g:mmol;
[0018] In step (2), the temperature of heating and stirring before adding copper nitrate trihydrate (Cu(NO3)2·3H2O) is 75-85°C, and the temperature of heating and stirring after adding copper nitrate trihydrate (Cu(NO3)2·3H2O) is 55-65°C and the time is 25-35 min;
[0019] In step (2), the vacuum drying is carried out at a temperature of 75 to 85° C. and for a time of 9 to 15 hours.
[0020] Further preferably, in step (3), the calcination temperature is 690-710° C. and the calcination time is 1.5-2.5 h.
[0021] 2. The preparation method of the above-mentioned solid magnesium-based hydrogen storage material is as follows:
[0022] MgH2 and copper niobate (CuNb2O6) are mixed and placed in a ball mill for dry ball milling for 9 to 15 hours to obtain a copper niobate-doped solid magnesium-based hydrogen storage material.
[0023] Preferably, the ball-to-material ratio of the dry ball milling is 18:0.9 to 22:1.1, and the ball milling time is 9 to 15 hours.
[0024] Preferably, the ball milling steel balls used in the dry ball milling process are obtained by mixing two types of steel balls with a diameter of 8 mm and a diameter of 5 mm in a mass ratio of 2.5 to 3.5 to 6.5 to 7.5.
[0025] Preferably, the dry ball milling program is specifically set as follows: the ball mill rotates forward for 8 to 12 minutes, pauses for 8 to 12 minutes, and then continues to rotate reversely for 8 to 12 minutes, and the revolution speed of the ball mill is 300 to 500 rpm.
[0026] 3. Application of the above copper niobate-doped solid magnesium-based hydrogen storage material in hydrogen storage.
[0027] The beneficial effects of the present invention are as follows: the present invention discloses a copper niobate-doped solid magnesium-based hydrogen storage material, which mainly involves doping copper niobate (CuNb2O6) into MgH2 by ball milling, and using CuNb2O6 to catalytically modify MgH2, thereby significantly improving the hydrogen absorption and desorption rates of MgH2, thereby obtaining a composite hydrogen storage material with excellent low-temperature hydrogen storage performance, while achieving joint optimization and improvement of hydrogen absorption kinetics and the total amount of hydrogen absorption and desorption. Compared with single metal oxides and bimetallic elements added in other forms, the catalytic improvement effect can be further optimized and improved by introducing new phases, thereby providing an effective strategy for the design of new magnesium-based composite hydrogen storage materials.
[0028] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0030] Figure 1 The XRD pattern (a) and XPS pattern (b) of the CuNb2O6 catalyst powder prepared in Example 1;
[0031] Figure 2 a and b are SEM images of 3 μm and 1 μm of the CuNb2O6 catalyst powder prepared in Example 1, c is a TEM bright field image of the CuNb2O6 catalyst powder prepared in Example 1, d to g are EDS mapping images of different elements of the CuNb2O6 catalyst powder prepared in Example 1, and h is a TEM high-resolution image of the CuNb2O6 catalyst powder prepared in Example 1;
[0032] Figure 3 The isothermal hydrogen release diagram (a) at 300°C and the isothermal hydrogen absorption diagram (b) at 150°C of the solid magnesium-based hydrogen storage material doped with copper niobate at different contents prepared in Examples 1 to 3;
[0033] Figure 4Wherein a is the isothermal hydrogen desorption curve of MgH2-3CuNb2O6 prepared in Example 1 at 225°C, 250°C, 275°C and 300°C, b is the isothermal hydrogen desorption curve of MgH2-3CuNb2O6 prepared in Example 1 at 200°C, c is the isothermal hydrogen absorption curve of MgH2-3CuNb2O6 prepared in Example 1 at 50°C, 100°C and 150°C, and d is the isothermal hydrogen absorption curve of MgH2-3CuNb2O6 prepared in Example 1 at 30°C;
[0034] Figure 5 Isothermal hydrogen desorption curves (a) at 250°C and isothermal hydrogen absorption curves (b) at 100°C of MgH2-3CuNb2O6 prepared in Example 1, MgH2-3CuO prepared in Comparative Example 1, MgH2-3Nb2O5 prepared in Comparative Example 2 and MgH2-3(CuO+Nb2O5) prepared in Comparative Example 3;
[0035] Figure 6 is the isothermal hydrogen absorption and desorption cycle curve of MgH2-3CuNb2O6 prepared in Example 1 at 300°C;
[0036] Figure 7 a and b are the XRD patterns of MgH2-3CuNb2O6 prepared in Example 1 and its comparison after ball milling, dehydrogenation, hydrogen absorption and fifty dehydrogenation cycles;
[0037] Figure 8 In the figure a is the XPS spectrum of Nb 3d of CuNb2O6 catalyst powder, and in the figure b, c and d are the XPS spectra of Nb 3d of MgH2-20CuNb2O6 in comparative example 4 in the dehydrogenation state, the hydrogen absorption state and after fifty dehydrogenation cycles. DETAILED DESCRIPTION
[0038] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and the features in the embodiments can be combined with each other without conflict.
[0039] Example 1
[0040] A copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-3CuNb2O6), the specific preparation method is as follows:
[0041] 1. Preparation of copper niobate (CuNb2O6): (1) First, weigh 2mmol Nb2O5 and dissolve it in 20ml hydrofluoric acid (HF), heat and stir in a water bath at 80°C for 30min, and after it is completely dissolved, add 80ml ammonia water (NH3·H2O) while stirring, then filter and wash to obtain a white precipitate; (2) Add the white precipitate and 10g citric acid (CA) to 100ml deionized water, heat and stir in a water bath at 80°C until it is completely dissolved, continue to add 2mmol Cu(NO3)2·3H2O, adjust the water bath temperature to 60°C and stir for 30min, after mixing evenly, put it into a vacuum drying oven, vacuum dry it at 80°C for 12h to obtain a dried solid; (3) Place the dried solid in a muffle furnace and calcine it at 700°C for 2h to obtain copper niobate (CuNb2O6 catalyst powder) with a particle size range of 200 to 500nm.
[0042] 2. Preparation of copper niobate-doped solid magnesium-based hydrogen storage material: Mix 97g MgH2 and 3g copper niobate (CuNb2O6) and place them in a ball mill for dry ball milling (the ball milling steel balls used are two kinds of steel balls with diameters of 8mm and 5mm mixed in a mass ratio of 3:7, the ball-to-material ratio is 20:1, the ball milling time is 12h, and the dry ball milling program is specifically set as: the ball mill rotates forward for 10min, pauses for 10min, and then continues to reverse for 10min) for 12h to obtain copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-3CuNb2O6).
[0043] Example 2
[0044] A copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-6CuNb2O6), the specific preparation method is as follows:
[0045] The step (2) of Example 1, "mixing 97 g MgH2 and 3 g copper niobate (CuNb2O6)" is modified to "mixing 94 g MgH2 and 6 g copper niobate (CuNb2O6)", and the rest of the method is the same as that of Example 1, so as to prepare a copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-6CuNb2O6).
[0046] Example 3
[0047] A copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-9CuNb2O6), the specific preparation method is as follows:
[0048] The step (2) of Example 1, "mixing 97 g MgH2 and 3 g copper niobate (CuNb2O6)" is modified to "mixing 91 g MgH2 and 9 g copper niobate (CuNb2O6)", and the rest of the method is the same as that of Example 1, to prepare a copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-9CuNb2O6).
[0049] Example 4
[0050] A copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-3CuNb2O6), the specific preparation method is as follows:
[0051] 1. Preparation of copper niobate (CuNb2O6): (1) First, weigh 2.5 mmol Nb2O5 and dissolve it in 20 ml of hydrofluoric acid (HF), heat and stir in a water bath at 85°C for 35 minutes, and after it is completely dissolved, add 85 ml of ammonia water (NH3·H2O) while stirring, and then filter and wash to obtain a white precipitate; (2) Add the white precipitate and 15 g of citric acid (CA) to 100 ml of deionized water, and heat and stir in a water bath at 85°C until it is completely dissolved, continue to add 2.5 mmol Cu(NO3)2·3H2O, adjust the water bath temperature to 65°C and stir for 35 minutes, after mixing evenly, put it into a vacuum drying oven, and vacuum dry it at 85°C for 15 hours to obtain a dried solid; (3) Place the dried solid in a muffle furnace and calcine it at 710°C for 2.5 hours to obtain copper niobate (CuNb2O6 catalyst powder) with a particle size range of 200 to 500 nm.
[0052] 2. Preparation of copper niobate-doped solid magnesium-based hydrogen storage material: Mix 97g MgH2 and 3g copper niobate (CuNb2O6) and place them in a ball mill for dry ball milling (the ball milling steel balls used are two kinds of steel balls with diameters of 8mm and 5mm mixed in a mass ratio of 3:7, the ball-to-material ratio is 22:1.1, the ball milling time is 15h, and the dry ball milling program is specifically set as: the ball mill rotates forward for 12min, pauses for 12min, and then continues to reverse for 12min) for 12h to obtain copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-3CuNb2O6).
[0053] Example 5
[0054] A copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-3CuNb2O6), the specific preparation method is as follows:
[0055] 1. Preparation of copper niobate (CuNb2O6): (1) First, weigh 1.5 mmol Nb2O5 and dissolve it in 20 ml of hydrofluoric acid (HF). Heat and stir in a water bath at 75°C for 25 min. After it is completely dissolved, add 85 ml of ammonia water (NH3·H2O) while stirring, and then filter and wash to obtain a white precipitate; (2) Add the white precipitate and 7.5 g of citric acid (CA) to 100 ml of deionized water, heat and stir in a water bath at 75°C until it is completely dissolved, continue to add 1.5 mmol Cu(NO3)2·3H2O, adjust the water bath temperature to 55°C and stir for 25 min. After mixing evenly, put it in a vacuum drying oven and vacuum dry it at 75°C for 9 h to obtain a dried solid; (3) Place the dried solid in a muffle furnace and calcine it at 690°C for 1.5 h to obtain copper niobate (CuNb2O6 catalyst powder) with a particle size range of 200 to 500 nm.
[0056] 2. Preparation of copper niobate-doped solid magnesium-based hydrogen storage material: 97 g MgH2 and 3 g copper niobate (CuNb2O6) were mixed and placed in a ball mill for dry ball milling (the ball milling steel balls used were obtained by mixing two steel balls with a diameter of 8 mm and a diameter of 5 mm in a mass ratio of 2.5:6.5, the ball-to-material ratio was 20:1, the ball milling time was 12 h, and the dry ball milling program was specifically set as: the ball mill rotated forward for 8 min, paused for 8 min, and then continued to reverse for 8 min) for 8 h to obtain copper niobate-doped solid magnesium-based hydrogen storage material (MgH2-3CuNb2O6).
[0057] Comparative Example 1
[0058] A copper oxide-doped solid magnesium-based hydrogen storage material (MgH2-3CuO), the preparation method of which is specifically as follows:
[0059] The step (2) in Example 1, "mixing 97 g MgH2 and 3 g copper niobate (CuNb2O6)" is modified to "mixing 97 g MgH2 and 3 g copper oxide (CuO)", which is prepared according to the method in Example 1 to obtain a copper oxide-doped solid magnesium-based hydrogen storage material (MgH2-3CuO).
[0060] Comparative Example 2
[0061] A niobium oxide-doped solid magnesium-based hydrogen storage material (MgH2-3Nb2O5), the preparation method of which is specifically as follows:
[0062] The step (2) in Example 1, "mixing 97 g MgH2 and 3 g copper niobate (CuNb2O6)" is modified to "mixing 97 g MgH2 and 3 g niobium oxide (Nb2O5)", which is prepared according to the method in Example 1 to obtain a copper oxide-doped solid magnesium-based hydrogen storage material (MgH2-3Nb2O5).
[0063] Comparative Example 3
[0064] A solid magnesium-based hydrogen storage material (MgH2-3 (CuO+Nb2O5)) doped with copper oxide and niobium oxide, the preparation method of which is as follows:
[0065] The step (2) in Example 1, “mixing 97 g MgH2 and 3 g copper niobate (CuNb2O6)”, is modified to “mixing 97 g MgH2, 0.7 g copper oxide and 2.3 g niobium oxide (Nb2O5)”, which is prepared according to the method in Example 1 to obtain a solid magnesium-based hydrogen storage material (MgH2-3(CuO+Nb2O5)) doped with copper oxide and niobium oxide.
[0066] Comparative Example 3
[0067] A copper oxide-doped solid magnesium-based hydrogen storage material (MgH2-20CuO), the preparation method of which is specifically as follows:
[0068] The step (2) in Example 1, "mixing 97 g MgH2 and 3 g copper niobate (CuNb2O6)" is modified to "mixing 80 g MgH2 and 20 g copper oxide (CuO)", which is prepared according to the method in Example 1 to obtain a copper oxide-doped solid magnesium-based hydrogen storage material (MgH2-20CuO).
[0069] Performance Testing
[0070] The CuNb2O6 catalyst powder prepared in Example 1 was subjected to XRD and XPS tests, and the results were as follows: Figure 1 As shown in a and b. Figure 1 It can be seen that the preparation method in Example 1 of the present invention can indeed prepare copper niobate (CuNb2O6).
[0071] Figure 2 a and b are SEM images of 3μm and 1μm of the CuNb2O6 catalyst powder prepared in Example 1, c is a TEM bright field image of the CuNb2O6 catalyst powder prepared in Example 1, d-g are EDS mapping images of different elements of the CuNb2O6 catalyst powder prepared in Example 1, and h is a TEM high-resolution image of the CuNb2O6 catalyst powder prepared in Example 1. Figure 2It can be seen that the CuNb2O6 catalyst prepared by the sol-gel method of the present invention is in the form of nanoparticles with a particle size range of 200-500nm. Figure 2 The TEM image in Figure c also shows that the CuNb2O6 catalyst prepared by the present invention is irregular CuNb2O6 nanoparticles. Figure 2 In (d-g), it can be observed that Cu, Nb and O elements are evenly distributed in the CuNb2O6 catalyst. In addition, Figure 2 Figure h is a high-resolution TEM image, from which we can see lattice fringes with a lattice spacing of 0.297 nm, and the fringes correspond to the (-131) crystal plane of CuNb2O6.
[0072] Figure 3 The isothermal hydrogen release diagram (a) at 300°C and the isothermal hydrogen absorption diagram (b) at 150°C of the solid magnesium-based hydrogen storage materials doped with copper niobate at different contents prepared in Examples 1 to 3. Figure 3 It can be seen in (a) that the solid magnesium-based hydrogen storage materials MgH2-3CuNb2O6, MgH2-6CuNb2O6, and MgH2-9CuNb2O6 formed after magnesium hydride is doped with 3wt.%, 6wt.%, and 9wt.% CuNb2O6 in Examples 1 to 3 can release 5.88wt.%, 5.51wt.%, and 5.47wt.% hydrogen within 3 minutes at 300°C, respectively. Before the dehydrogenation process is completely completed, MgH2-3CuNbO and MgH2-6CuNbO have faster dehydrogenation rates than MgH2-9CuNbO. As the doping ratio of CuNb2O6 increases, MgH2-3CuNbO has a greater hydrogen desorption capacity than MgH2-6CuNbO. In addition, according to Figure 3 It can be seen from (b) that before reaching hydrogen absorption saturation, the three composite materials with different doping ratios have the same hydrogen absorption rate. However, as in the hydrogen desorption process, the lower the doping ratio, the greater the hydrogen absorption capacity. MgH2-3CuNbO, MgH2-6CuNbO and MgH2-9CuNbO can absorb 5.5wt.%, 5.32wt.% and 4.88wt.% hydrogen in 1 minute, respectively. Comprehensively considered, doping 3wt.% CuNb2O6 catalyst has the best effect on improving the hydrogen absorption and desorption performance of magnesium hydride.
[0073] Figure 4Where a is the isothermal hydrogen desorption curve of MgH2-3CuNb2O6 prepared in Example 1 at 225°C, 250°C, 275°C and 300°C, b is the isothermal hydrogen desorption curve of MgH2-3CuNb2O6 prepared in Example 1 at 200°C, c is the isothermal hydrogen absorption curve of MgH2-3CuNb2O6 prepared in Example 1 at 50°C, 100°C and 150°C, and d is the isothermal hydrogen absorption curve of MgH2-3CuNb2O6 prepared in Example 1 at 30°C. Figure 4 As can be seen from a and b, after adding the CuNb2O6 catalyst to form MgH2-3CuNb2O6, the dehydrogenation kinetics of the Mg / MgH2 system is significantly enhanced, with a very fast dehydrogenation rate and the largest hydrogen release capacity at 300°C, that is, 5.8wt.% hydrogen can be released within 2.5min. When the temperature is reduced to 250°C, MgH2-3CuNbO can also maintain a high hydrogen release rate and a high amount of hydrogen release, that is, 5.53wt.% hydrogen can be released within 6min. Even if the temperature is reduced to 200°C, MgH2-3CuNbO can still dehydrogenate, with 3.74wt.% hydrogen released within 150min. It can be seen from the above results that after doping with the CuNb2O6 catalyst, the dehydrogenation kinetics of magnesium hydride are greatly enhanced. Figure 4 Figures c and d show the isothermal hydrogen absorption curves of MgH2-3CuNbO at different temperatures. The composite system has good hydrogen absorption performance. At 150°C, it can absorb 5.5wt.% hydrogen within 1 minute, and at a low temperature of 50°C, it can also absorb 2.01wt.% hydrogen in 30 minutes. In addition, even at room temperature, MgH2-3CuNbO has the ability to absorb hydrogen, and can absorb 1.75wt.% hydrogen within 60 minutes.
[0074] Figure 5 The isothermal hydrogen desorption curves (a) at 250°C and the isothermal hydrogen absorption curves (b) at 100°C of MgH2-3CuNb2O6 prepared in Example 1, MgH2-3CuO prepared in Comparative Example 1, MgH2-3Nb2O5 prepared in Comparative Example 2 and MgH2-3(CuO+Nb2O5) prepared in Comparative Example 3 are shown in Table 1. Figure 5As can be seen in a, within 5 minutes, MgH2-3CuNbO, MgH2-3CuO, MgH2-3Nb2O5 and MgH2-3(CuO+Nb2O5) can release 5.32wt.%, 0.17wt.%, 0.71wt.% and 0.53wt.% of hydrogen respectively. The MgH2-3CuNbO composite system has the largest hydrogen decomposition capacity, and the hydrogen decomposition rate of this system is much greater than that of other single metal composite systems in the first few minutes. Although MgH2-3(CuO+Nb2O5) can achieve the same amount of hydrogen decomposition as MgH2-3CuNbO, its complete hydrogen decomposition time takes 40 minutes, while MgH2-3CuNbO only takes 7 minutes. Figure 5 As shown in b, the four composite materials of MgH2-3CuNbO, MgH2-3CuO, MgH2-3Nb2O5 and MgH2-3(CuO+Nb2O5) can absorb 3.95wt.%, 1.14wt.%, 2.79wt.% and 2.84wt.% of hydrogen respectively within 5 minutes. MgH2-3CuNbO has the fastest hydrogen absorption rate and the largest hydrogen absorption capacity. In summary, the hydrogen absorption and desorption performance of the MgH2-3CuNbO composite system is better than that of other single metal compound systems and single metal compound mixed systems.
[0075] Figure 6 The isothermal hydrogen absorption and desorption cycle curve of MgH2-3CuNb2O6 prepared in Example 1 at 300°C. Figure 6 It can be seen that in the first ten cycles of hydrogen absorption and desorption, the hydrogen storage capacity dropped sharply, and the hydrogen absorption and desorption rate also gradually decreased. In the process of hydrogen absorption and desorption after the tenth cycle, the hydrogen storage capacity gradually reached a stable state, from 5.97wt.% in the first cycle to 5.21wt.% in the fiftieth cycle, and the hydrogen storage capacity remained at 87%.
[0076] Figure 7 Figures a and b are XRD patterns of MgH2-3CuNb2O6 prepared in Example 1 and MgH2-20CuNb2O6 prepared in Comparative Example 4 after ball milling, dehydrogenation, hydrogen absorption and fifty dehydrogenation cycles. Figure 7 As can be seen in a, due to the small amount of catalyst (CuNb2O6) added, only the diffraction peaks of Mg, MgH2 and MgO can be found in the spectrum, and there are no other diffraction peaks related to CuNb2O6. In order to more clearly illustrate the catalytic mechanism of CuNb2O6 catalyst, we increased the doping amount of CuNb2O6 to 20wt.%, and performed XRD and TEM tests on the MgH2-20CuNb2O6 composite materials in different states. The products of MgH2-20CuNb2O6 at different stages are as follows Figure 7As shown in b, the main phase of the ball-milled sample is magnesium hydride, and there is a small amount of MgO impurity phase. In the first hydrogen release and the hydrogen release sample after fifty cycles, the main phase is Mg, but the diffraction peaks corresponding to the Mg2Cu phase can be found at 20°, 35.1°, 39.4° and 44.6°. In addition, in the hydrogen absorption sample, in addition to the main phase MgH2, the diffraction peaks corresponding to the MgCu2 phase were found at 21.8°, 42.6° and 44.6°. From the XRD spectra of the MgH2-20CuNb2O6 composite material during hydrogen release, hydrogen absorption and cycle, it can be seen that during the first hydrogen release process of the composite material, the CuNb2O6 catalyst reacted with magnesium hydride to produce a new Mg2Cu phase, and reacted again during the hydrogen absorption process, and the Mg2Cu phase transformed into the MgCu2 phase.
[0077] Figure 8 a is the XPS spectrum of Nb 3d of CuNb2O6 catalyst powder, b, c and d are the XPS spectra of Nb 3d of MgH2-20CuNb2O6 in Comparative Example 4 in the dehydrogenation state, the hydrogen absorption state and the state after fifty dehydrogenation cycles. Figure 8 It can be seen that after the CuNb2O6 catalyst is composited with MgH2, the binding energy position of the pentavalent Nb element (3d3 / 2209.81eV and 3d5 / 2207.05eV) in the pure catalyst is significantly lower than that in the pure catalyst. Figure 8 As shown in a), after the first release of hydrogen ( Figure 8 As shown in b), after the first hydrogen absorption ( Figure 8 c) and after fifty cycles ( Figure 8 The binding energy position of the Nb element (shown in d) shifts to the right, indicating that the high-valent Nb is reduced by magnesium hydride, and the original pentavalent Nb is reduced to tetravalent Nb (3d3 / 2209.23eV and 3d5 / 2206.53eV), divalent Nb (3d3 / 2206.19eV and 3d5 / 2203.49eV) and elemental Nb (3d3 / 2204.78eV and 3d5 / 2201.94eV). It can be seen that the Nb element of the CuNb2O6 catalyst finally exists stably in magnesium hydride in the form of multiple valence states such as NbO2, NbO and Nb, catalyzing the absorption and desorption of hydrogen by magnesium hydride.
[0078] Similarly, the performance test in the above-mentioned Example 1 was carried out on the MgH2-3CuNb2O6 prepared in Example 4 and Example 5, and the results were similar to the performance of the MgH2-3CuNb2O6 prepared in Example 1.
[0079] In summary, the present invention discloses a copper niobate-doped solid magnesium-based hydrogen storage material, which mainly involves doping copper niobate (CuNb2O6) into MgH2 by ball milling, and using CuNb2O6 to catalytically modify MgH2, thereby significantly improving the hydrogen absorption and desorption rate of MgH2, and obtaining a composite hydrogen storage material with excellent low-temperature hydrogen storage performance, while achieving the joint optimization and improvement of hydrogen absorption kinetics and the total amount of hydrogen absorption and desorption. Compared with single metal oxides and bimetallic elements added in other forms, the catalytic improvement effect can be further optimized and improved by introducing new phases, providing an effective strategy for the design of new magnesium-based composite hydrogen storage materials. In addition, the present invention also discloses a method for preparing a copper niobate-doped solid magnesium-based hydrogen storage material, which mainly involves mixing MgH2 and doped copper niobate (CuNb2O6) and placing them in a ball mill, and then dry milling. The preparation method of the present invention promotes the mixing of the added catalyst copper niobate (CuNb2O6) with MgH2 and uniformly distributing them on the surface of MgH2. On the other hand, the ball milling method used in the preparation method of the present invention can refine the grain size, increase the specific surface area of MgH2 particles, increase the active centers of the catalyst, expand the reaction area, shorten the diffusion distance, provide more diffusion channels, and accelerate the adsorption and diffusion of hydrogen atoms.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A copper niobate-doped solid magnesium-based hydrogen storage material, characterized in that: The solid magnesium-based hydrogen storage material includes MgH2 and doped copper niobate; The mass ratio of MgH2 to copper niobate is 0.91:0.09 to 0.97:0.
03.
2. The solid magnesium-based hydrogen storage material according to claim 1, characterized in that: The copper niobate is prepared according to the following method: (1) Dissolve niobium oxide in hydrofluoric acid, heat and stir to dissolve it, add ammonia water while stirring, react for 10 minutes, filter and wash to obtain a white precipitate; (2) adding the white precipitate and citric acid into water, heating and stirring to dissolve them, adding copper nitrate trihydrate, continuing heating and stirring to mix them evenly, and vacuum drying; (3) placing the vacuum-dried solid in step (2) in a muffle furnace and calcining to obtain copper niobate.
3. The solid magnesium-based hydrogen storage material according to claim 2, characterized in that: In step (1), the molar ratio of niobium oxide to ammonia water is less than or equal to 1:1, and the heating and stirring temperature is 75 to 85° C. and the time is 25 to 35 minutes.
4. The solid magnesium-based hydrogen storage material according to claim 2, characterized in that: The molar mass ratio of the niobium oxide in step (1) to the citric acid and copper nitrate trihydrate in step (2) is 1.5:7.5:1.5-2.5:12.5:2.5, mmol:g:mmol; In step (2), the temperature of heating and stirring before adding copper nitrate trihydrate is 75-85° C., and the temperature of heating and stirring after adding copper nitrate trihydrate is 55-65° C. and the time is 25-35 min; In step (2), the vacuum drying is carried out at a temperature of 75 to 85° C. and for a time of 9 to 15 hours.
5. The solid magnesium-based hydrogen storage material according to claim 2, characterized in that: In step (3), the calcination temperature is 690-710° C. and the calcination time is 1.5-2.5 h.
6. The method for preparing the solid magnesium-based hydrogen storage material according to any one of claims 1 to 5, characterized in that: The preparation method is specifically as follows: MgH2 and copper niobate are mixed and placed in a ball mill for dry ball milling for 9 to 15 hours to obtain a copper niobate-doped solid magnesium-based hydrogen storage material.
7. The preparation method according to claim 6, characterized in that: The ball-to-material ratio of the dry ball milling is 18:0.9-22:1.1, and the ball milling time is 9-15 hours.
8. The preparation method according to claim 6, characterized in that: The ball milling steel balls used in the dry ball milling process are obtained by mixing two kinds of steel balls with diameters of 8 mm and 5 mm in a mass ratio of 2.5-3.5:6.5-7.
5.
9. The preparation method according to claim 6, characterized in that: The dry ball milling program is specifically set as follows: the ball mill rotates forward for 8 to 12 minutes, pauses for 8 to 12 minutes, and then continues to rotate backward for 8 to 12 minutes. The revolution speed of the ball mill is 300 to 500 rpm.
10. Use of the copper niobate-doped solid magnesium-based hydrogen storage material according to any one of claims 1 to 5 in hydrogen storage.